Iron mapping using the temperature dependency of the magnetic susceptibility. Issue 3 (17th April 2014) - Birkl, Christoph; Langkammer, Christian; Krenn, Heinz; Goessler, Walter; Ernst, Christina; Haybaeck, Johannes; Stollberger, Rudolf; Fazekas, Franz; Ropele, Stefan
<x xml:space="preserve">Abstract</x> Purpose The assessment of iron content in brain white matter (WM) is of high importance for studying neurodegenerative diseases. While R2* mapping and quantitative susceptibility mapping is suitable for iron mapping in gray matter, iron mapping in WM still remains an unsolved problem. We propose a new approach for iron mapping, independent of diamagnetic contributions of myelin by assessing the temperature dependency of the paramagnetic susceptibility. Theory and Methods We used unfixed human brain slices for relaxometry and calculated R2′ as a measure for microscopic susceptibility variations at several temperatures (4°C–37°C) at 3 Tesla. The temperature coefficient of R2′ (TcR2p) was calculated by linear regression and related to the iron concentration found by subsequent superconducting quantum interference device (SQUID) magnetometry and by inductively coupled plasma mass spectrometry. Results In line with SQUID measurements, R2′ mapping showed a linear temperature dependency of the bulk susceptibility with the highest slope in gray matter. Even in WM, TcR2p yielded a high linear correlation with the absolute iron concentration. Conclusion According to Curie's law, only paramagnetic matter exhibits a temperature dependency while the diamagnetism shows no effect. We have demonstrated that the temperature coefficient (TcR2p) can be used as a measure of the paramagnetic susceptibility despite of an unknown diamagnetic background. Magn Reson Med 73:1282–1288, 2015. © 2014 Wiley Periodicals, Inc.